Data center energy efficiency case and energy saving operation - Jieliang LOU (Dianxin kexue)
PUE value is the key indicator of energy efficiency in data center.Through the comparative analysis of refrigeration efficiency,cooling efficiency,energy conversion efficiency and energy transmission efficiency,the reasons for difference in PUE between two data center cases were found.Three measures on the strategy of energy-saving operation of data center were put forward,as to control the number of refrigerators,to reduce the temperature of cooling water and to raise the temperature of chilled water.Some inspirations on energy saving in the construction and operation of the data center were raised.